2003
DOI: 10.1016/s0896-6273(03)00467-7
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Neural Representation of Intensity and Affective Valuation in Human Gustation

Abstract: We used a 2 x 2 factorial design to dissociate regions responding to taste intensity and taste affective valence. Two intensities each of a pleasant and unpleasant taste were presented to subjects during event-related fMRI scanning. The cerebellum, pons, middle insula, and amygdala responded to intensity irrespective of valence. In contrast, valence-specific responses were observed in anterior insula/operculum extending into the orbitofrontal cortex (OFC). The right caudolateral OFC responded preferentially to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

59
543
9
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 716 publications
(615 citation statements)
references
References 74 publications
59
543
9
4
Order By: Relevance
“…Importantly, only controls, but not recovered AN, showed a positive relationship between self-ratings of pleasantness and the intensity of the signal for sugar in the insula, ventral, and dorsal putamen as well as anterior cingulate cortex. Consistent with these findings Small et al (2001Small et al ( , 2003a found valence-specific responses in the anterior insula/operculum, OFC, and anterior cingulate cortex in healthy subjects. In contrast, amygdala activity was driven by stimulus intensity irrespective of valence.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Importantly, only controls, but not recovered AN, showed a positive relationship between self-ratings of pleasantness and the intensity of the signal for sugar in the insula, ventral, and dorsal putamen as well as anterior cingulate cortex. Consistent with these findings Small et al (2001Small et al ( , 2003a found valence-specific responses in the anterior insula/operculum, OFC, and anterior cingulate cortex in healthy subjects. In contrast, amygdala activity was driven by stimulus intensity irrespective of valence.…”
Section: Discussionsupporting
confidence: 68%
“…In general, the anterior, less differentiated half of the insula receives the majority of projections from the amygdala and thalamic taste centers, making it an ideal site for the formulation of hedonic representations of taste. Consistent with this, anterior portions of the insula have been shown to be differentially activated to the intensity and valence of pleasant and unpleasant tastes (Small et al, 2003a), and are thus important to examine in the eating disordered population.…”
Section: Discussionmentioning
confidence: 68%
“…Although taste stimulation has consistently activated the same brain regions across multiple f MRI studies, including insula and overlaying operculum, the transduction mechanisms remain incompletely characterised. Previous studies reported the primary taste cortex is located within the anterior insula/frontal operculum (13)(14)(15) with secondary projections to the orbitofrontal cortex (OFC) (16) , amygdala (17) , anterior cingulate cortex (ACC) (18) , ventral striatum (19) and dorsolateral prefrontal cortex (20) . O'Doherty et al were the first to investigate the cortical response to pleasant (glucose) and aversive (salt) taste stimuli by assessing stimuli against a tasteless control stimulus (21) .…”
Section: Functional Mri Responses To Taste Aroma and Oral Somatosensmentioning
confidence: 99%
“…In humans, neuroimaging studies have found that the affective valence of pleasure may be coded separately from sensation intensity in a network of brain regions (Anderson and Sobel 2003;Gottfried et al 2002;Rolls et al 2003;Small et al 2003). As an example, taste intensity (but not valence) was coded by anterior insula cortex activity (primary gustatory area), while subjective pleasantness was coded by activity in medial orbitofrontal cortex, midinsular cortex, and in the anterior cingulate cortex (de Araujo et al 2003c;Figs.…”
Section: Cortical Cognition and Pleasurementioning
confidence: 99%